Harlequin Ichthyosis - Ahmad Hashemzadeh; Farhad Heydarian (Acta Medica Iranica, 2009)
It is an autosomal recessive, and occasionally autosomal dominant mutant extremely rare disorder with only 100 reported case in literature. This fatal disorder occur in both sexes and all races. In most circumstances the newborn die soon after birth Also it is known as harlequin fetus, alligator baby or keratosis diffusa fatalis. Because of its rarity, we report 2 cases of this disorder, here.